Balloon pulmonary angioplasty for inoperable chronic thromboembolic pulmonary hypertension: the UK experience. Issue 1 (27th February 2020) - Hoole, Stephen P; Coghlan, John G; Cannon, John E; Taboada, Dolores; Toshner, Mark; Sheares, Karen; Fletcher, Andrew John; Martinez, Guillermo; Ruggiero, Alessandro; Screaton, Nicholas; Jenkins, David; Pepke-Zaba, Joanna
Abstract : Objective: Inoperable chronic thromboembolic pulmonary hypertension (CTEPH) managed medically has a poor prognosis. Balloon pulmonary angioplasty (BPA) offers a new treatment for inoperable patients. The national BPA service for the UK opened in October 2015 and we now describe the treatment of our initial patient cohort. Methods: Thirty consecutive, inoperable, anatomically suitable, symptomatic patients on stable medical therapy for CTEPH were identified and offered BPA. They initially underwent baseline investigations including Cambridge Pulmonary Hypertension Outcome Review (CAMPHOR) quality of life (QoL) questionnaire, cardiopulmonary exercise test, 6 min walk distance (6MWD), transthoracic echocardiography, N-terminal probrain natriuretic peptide (NT pro-BNP) and right heart catheterisation. Serial BPA sessions were then performed and after completion, the treatment effect was gauged by comparing the same investigations at 3 months follow-up. Results: A median of 3 (IQR 1–6) BPA sessions per patient resulted in a significant improvement in functional status (WHO functional class ≥3: 24 vs 4, p<0.0001) and QoL (CAMPHOR symptom score: 8.7±5.4 vs 5.6±6.1, p=0.0005) with reductions in pulmonary pressures (mean pulmonary artery pressure: 44.7±11.0 vs 34.4±8.3 mm Hg, p<0.0001) and resistance (pulmonary vascular resistance: 663±281 vs 436±196 dyn.s.cm -5, p<0.0001). Exercise capacity improved (minute ventilation/carbon dioxide production: 55.3±12.2 vs 45.0±7.8, p=0.03 and 6MWD: 366±107 vs 440±94 m, p<0.0001) and there was reduction in right ventricular (RV) stretch (NT pro-BNP: 442 (IQR 168–1607) vs 202 (IQR 105–447) pg/mL, p<0.0001) and dimensions (mid RV diameter: 4.4±1.0 vs 3.8±0.7 cm, p=0.002). There were no deaths or life-threatening complications and the mild-moderate per-procedure complication rate was 10.5%. Conclusions: BPA is safe and improves the functional status, QoL, pulmonary haemodynamics and RV dimensions of patients with inoperable CTEPH.